Analisis Keterampilan Proses Sains Peserta Didik Kelas IX pada Materi Tekanan - Budiarti, Lia Wahyuningsih (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2025)
This study aims to describe the percentage and level of science process skills on the topic of pressure in Grade IX students of SMP Negeri 2 Sungai Kakap. The type of research used in this study is descriptive research. The sample was selected using purposive sampling. The instrument employed was a Science Process Skills (SPS) test. The research data were analyzed both quantitatively and qualitatively. The results showed that the Science Process Skills of Grade IX students of SMP Negeri 2 Sungai Kakap on the topic of pressure fell into the “good” category with an average percentage of 78%. Based on the five aspects analyzed, the results were as follows: observing skills reached 80% (good), classifying skills 85% (very good), communicating skills 76% (good), predicting skills 65% (good), and concluding skills 84% (very good). Keywords: Science Process Skills, Pressure, Physics